Effect of milk fat globules on growth and metabolism in rats fed an unbalanced diet - Argov-Argaman, Nurit; Altman, Hodaya; Janssen, Jerome Nicolas; Daeem, Seman; Raz, Chen; Mesilati-Stahy, Ronit; Penn, Svetlana; Monsonego-Ornan, Efrat (Frontiers in Nutrition, 2024)
We assessed the effects of supplementing milk fat globules (MFG) on the growth and development of the skeleton in rats fed a Western unbalanced diet (UBD). The UBD is high in sugar and fat, low in protein, fiber, and micronutrients, and negatively impacts health. The MFG—a complex lipid-protein assembly secreted into milk—has a unique structure and composition, which differs significantly from isolated and processed dietary ingredients. Rats consuming the UBD exhibited growth retardation and disrupted bone structural and mechanical parameters; these were improved by supplementation with small MFG. The addition of small MFG increased the efficiency of protein utilization for growth, and improved trabecular and cortical bone parameters. Furthermore, consumption of UBD led to a decreased concentration of saturated fatty acids and increased levels of polyunsaturated fatty acids (PUFA), particularly omega-6 PUFA, in the serum, liver, and adipose tissue. The addition of small MFG restored PUFA concentration and the ratio of omega-6 to omega-3 PUFA in bone marrow and adipose tissue. Finally, large but not small MFG supplementation affected the cecal microbiome in rats. Overall, our results suggest that natural structure MFG supplementation can improve metabolism and bone development in rats fed an UBD, with the effects depending on MFG size. Moreover, the benefits of small MFG to bone development and metabolism were not mediated by the microbiome, as the detrimental effects of an UBD on the microbiome were not mitigated by MFG supplementation.